A New Competition: Changes in the Flow of Fruit Commodities Sales in Kalianda District, South Lampung Regency, Indonesia - Nabillah, Ratu; Abubakar, Kamaru; Rijanta, R; Harini, Rika (Tunas Geografi, 2023)
The COVID-19 pandemic transformed the industry into the strongest online industry of the last decade. One of the commodities that have experienced faster sales since the COVID-19 pandemic is healthy food; fruit is one of them. As a response to the crisis, online fruit traders have emerged using social media. Unfortunately, not all community groups can adapt to technology. Fruit traders who stay in the kiosk (selling offline) are included in the new left-behind group due to their inability to technology adaptation. This study aims to differentiate the sales flow of fruit commodities (before and after the appearance of online sales) and describe the advantages and disadvantages of each group (online traders and kiosk/offline traders). The data to answer the two research goals were processed in a qualitative descriptive way. The results show that online traders have a shorter sales flow than kiosk traders. The main advantages of online traders include using social media, which makes it easier to find market and customer information, low prices, and ownership of transportation. Meanwhile, the main disadvantages of offline fruit traders are the limited quantity of human resources, the inability to operate smartphones and social media, and not always having transportationKeywords: New Competition, Fruit Sales Flow, Online Trader, Kiosk Merchant